Ability to Report Emergency at Farmers in the Agriculture Area - Rizeki Dwi Fibriansari; Arista Maisyaroh; Eko Prasetya Widianto (NurseLine Journal, 2021)
Background: Low knowledge and motivation about using personal protective equipment on farmers can cause workplace accidents. Upper limb injuries comprise 67% of all injuries, and the most active parts are fingers (43%). Due to the high number of injuries among farmers, the community needs emergency services where this emergency condition requires immediate health services to reduce mortality and prevent disability. Purpose: This study aims to analyze the factors that affect farmers ability to report daily emergencies in the agricultural area of ​​Lumajang. Methods: The design of this study was cross-sectional. The research respondents were 62 farmers who were taken by purposive sampling. Data collection used a questionnaire consisting of knowledge of injury recognition, management, and emergency events reporting. Data analysis was bivariate analysis with the Chi-Square test. Results: Knowledge of farmers recognizing injuries with good categories as much as 92% (p = 0.042), knowledge of farmers doing injury management as much as 80.6% in good category (p = 0.000), and knowledge of reporting of daily emergency events in agricultural areas as much as 61, 3% is moderate (p = 0.000). Recognizing the causes of injury of farming areas will increase farmers' knowledge in managing injuries to seek assistance in handling victims quickly and accurately with useful reporting techniques. Conclusion: The ability to report emergency events in the agricultural area is still in an adequate category. We must continuously improve the socialization of standard operational procedures (SOP) regarding effective communication in reporting injury incidents at PSC 119 Lumajang District. Services provided are fast, precise, responsive, and alert to prevent disability and save someone's life from death.